1997
DOI: 10.1093/emboj/16.15.4531
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection of non-dividing cells: evidence that the amino-terminal basic region of the viral matrix protein is important for Gag processing but not for post-entry nuclear import

Abstract: Human immunodeficiency virus type‐1 (HIV‐1) is able to infect non‐dividing cells such as tissue macrophages productively because post‐entry viral nucleoprotein complexes are specifically imported into the nucleus in the absence of mitosis. Although it has been proposed that an amino‐terminal region of the viral matrix (MA, p17Gag) protein harbors a basic‐type nuclear localization sequence (NLS) that contributes to this process, utilization of three distinct nuclear import assays failed to provide any direct su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
264
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(272 citation statements)
references
References 61 publications
5
264
3
Order By: Relevance
“…The HIV-1 MA domain was reported previously to have two NLSs (5,21) and one NES (13), but multiple subsequent reports have shown that HIV-1 MA-GFP is excluded from the nucleus (2,10) and that it does not contain a conventional NLS (15,22). Two studies in the past year confirmed that HIV-1 Gag lacks a CRM1-dependent nuclear export signal (2,18).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The HIV-1 MA domain was reported previously to have two NLSs (5,21) and one NES (13), but multiple subsequent reports have shown that HIV-1 MA-GFP is excluded from the nucleus (2,10) and that it does not contain a conventional NLS (15,22). Two studies in the past year confirmed that HIV-1 Gag lacks a CRM1-dependent nuclear export signal (2,18).…”
Section: Discussionmentioning
confidence: 96%
“…(K to Q) Subcellular localization of FIV MA-CFP, CA-CFP, and NCp2-CFP. Transfected HeLa cells were treated or not with LMB for 3 h. The nuclear/total MFI (Q) was determined as described above for panel J for 158 cells (6,17,25,23,15,15,21,16,11, and 9 cells for columns from left to right, respectively). Images are representative of at least three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 MA contains two sequences that could act as an NLS (Bukrinsky et al, 1993;Haffar et al, 2000). MA NLS mutants were found to be unable to replicate in macrophages in some studies but not in others (Fouchier et al, 1997;Reil et al, 1998;von Schwedler et al, 1994). The third viral protein involved in nuclear import of HIV-1 PIC is the viral protein R (Vpr) (Heinzinger et al, 1994;Popov et al, 1998) which is present only in lentiviruses.…”
Section: Nuclear Importmentioning
confidence: 99%
“…Vpr and MA may cooperate for the nuclear import of the PIC (Haffar et al, 2000;Popov et al, 1998). However, viruses lacking MA NLS and Vpr (Vpr.NLS) are able to replicate in macrophages, albeit less efficiently than the wild-type virus (Fouchier et al, 1997;Kootstra and Schuitemaker, 1999). This suggests that Vpr and MA-NLS are not essential for HIV-1 replication in primary macrophages.…”
Section: Nuclear Importmentioning
confidence: 99%
“…Some functional assignments to proteins have also been contested [142][143][144][145] and the whole area of the mechanism of nuclear import is regarded as unsettled at present; for current summaries of these controversies, see [99,102]. There is general agreement that CA is not an HIV-1 PIC constituent but that some MA is retained, as well as IN and Vpr, and, in some studies, NC [146].…”
Section: Mechanisms Of Lentiviral Nuclear Import: Central Dna Flaps Amentioning
confidence: 99%